القدرة على قراءة المادة العربية لطلاب الصف الثامن بمدرسة العلوم المتوسطة الإسلامية المتكاملة ميدان - Mariana Pasaribu; Rahmaini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article describes the ability to read Arabic material in class VIII students at the Medan integrated Al Ulum Islamic Middle School where reading is an effort to find various information contained in writing. This means that reading is a thinking process to understand the content of the text or material being read. This research aims to determine: The ability to read Arabic material in class VIII students at Al Ulum Terpadu Islamic Middle School, Medan, Factors that influence the ability to read Arabic material in class VIII students at Al Ulum Terpadu Islamic Middle School, Medan. The research method used is descriptive qualitative where the researcher describes an object or phenomenon which is expressed in narrative writing. Data collection was carried out using observation, interviews and documentation techniques. The results of this research show that the ability to read Arabic material in class VIII students at Al Ulum Integrated Islamic Middle School in Medan means that the majority of students have problems in reading, especially in fluency and pronunciation of Arabic letters. Even though they receive tahfizul Qur'an lessons every week, as well as reading material in textbooks, the lack of reading practice is the main factor in their difficulties. Some students who have good reading skills usually come from Islamic boarding school backgrounds. When interviewed, many students expressed that they preferred learning English rather than Arabic because they found Arabic difficult to understand with its many rules and variations. Reading ability involves clarity of pronunciation, appreciation of content, fluency and understanding of punctuation.